Resprouting as a persistence strategy of tropical forest trees: relations with carbohydrate storage and shade tolerance - Poorter, Lourens; Kitajima, Kaoru; Mercado, Pablo; Chubiña, Jose; Melgar, Israel; Prins, Herbert H. T (Ecology (Durham), 2010)
Resprouting is an important persistence strategy for woody species and represents a dominant pathway of regeneration in many plant communities, with potentially large consequences for vegetation dynamics, community composition, and species coexistence. Most of our knowledge of resprouting strategies comes from fire-prone systems, but this cannot be readily applied to other systems where disturbances are less intense. In this study we evaluated sapling responses to stem snapping for 49 moist-forest species and 36 dry-forest species from two Bolivian tropical forests. To this end we compared in a field experiment the survival and height growth of clipped and control saplings for a two-year period, and related this to the shade tolerance, carbohydrate reserves, and the morphological traits (wood density, leaf size) of the species. Nearly all saplings resprouted readily after stem damage, although dry-forest species realized, on average, a better survival and growth after stem damage compared to moist-forest species. Shade-tolerant species were better at resprouting than light-demanding species in moist forest. This resprouting ability is an important prerequisite for successful regeneration in the shaded understory, where saplings frequently suffer damage from falling debris. Survival after stem damage was, surprisingly, only modestly related to stem reserves, and much more strongly related to wood density, possibly because a high wood density enables plants to resist fungi and pathogens and to reduce stem decay. Correlations between sapling performance and functional traits were similar for the two forest types, and for phylogenetically independent contrasts and for cross-species analyses. The consistency of these results suggests that tropical forest species face similar trade-offs in different sites and converge on similar sets of solutions. A high resprouting ability, as well as investments in stem defense and storage reserves, form part of a suite of co-evolved traits that underlies the growth-survival trade-off, and contributes to light gradient partitioning and species coexistence. These links with shade tolerance are important in the moist evergreen forest, which casts a deep, more persistent shade, but tend to diminish in dry deciduous forest where light is a less limiting resource.